Correlation among selected fracture‐mechanical parameters of concrete obtained from experiments and inverse analyses. (December 2016) - Zimmermann, Thomas; Lehký, David; Strauss, Alfred
Abstract: The correlations among selected parameters of concrete were investigated for concrete mixes of the strength classes C20/25, C25/30, C30/37, C40/50 and C50/60. The focus was laid on correlations between basic mechanical parameters such as compressive strength, tensile strength and modulus of elasticity as well as parameters related to concrete fracture, represented here by specific fracture energy. Laboratory tests examining the fracture behaviour and mechanical properties were carried out in order to determine the fundamental concrete parameters. In particular, standard compression tests on test cubes and three‐point bending tests on beams with central edge notch were performed. Additional material parameters were identified using the inverse analysis technique. Finally, correlation factors between different parameters of concrete were identified using the rank‐order correlation method.